A Pragmatic Analysis of Language Use of Nigerian Army on Parade Ground - Bamigbola, Esther Olayinka (International Journal of Language and Literary Studies, 2022)
In any society, it is generally believed that peaceful co-existence hinges on effective communication and understanding of the peculiarities of each section in the society. The generation of meaning is therefore a sine qua non of mutual relationships in a communication situation. This study examines the use of language in the daily routines of the Nigerian Army. It makes use of pragmatic tools to interpret the utterances and the symbolic actions that take place during parade exercises in the Nigerian Army. The study is empirical and the analysis is guided by Austin’s Speech Act theory, supported with Searle’s Indirect Speech Act and Bach and Harnish’s Intention and Inference. The data analyzed in the study were recorded during a parade in a Nigerian Army Division at Ilorin, Kwara State, Nigeria. Participant observation was also employed. The study reveals that context, mutual contextual beliefs and non-verbal communication are prominent pragmatic tools in the language of the Nigerian Army during parades. It was found that activities on the parade ground are carried out using both verbal and non-verbal means of communication. Symbols, dress and appearance are significant, non-verbal features in the Nigerian Army. The study also revealed that regular use of authority in the military mirrors the illocutionary force of command; therefore, the language is more often than not forceful rather than persuasive. As such ‘alerting’ ‘informing’ and ‘commanding’ acts are prominent acts in parade language.